Volumetric Brain Morphometry Changes in Patients with Obstructive Sleep Apnea Syndrome: Effects of CPAP Treatment and Literature Review - Huynh, Nelly T.; Prilipko, Olga; Kushida, Clete A.; Guilleminault, Christian (Frontiers in Neurology, 2014)
Introduction: Obstructive sleep apnea syndrome (OSAS) is a frequent breathing disorder occurring during sleep that is characterized by recurrent hypoxic episodes and sleep fragmentation. It remains unclear whether OSAS leads to structural brain changes, and if so, in which brain regions. Brain region-specific gray and white matter volume (GMV and WMV) changes can be measured with voxel-based morphometry (VBM). The aims of this study were to use VBM to analyze GMV and WMV in untreated OSAS patients compared to healthy controls (HC); examine the impact of OSAS-related variables (nocturnal hypoxemia duration and sleep fragmentation index) on GMV and WMV; and assess the effects of therapeutic versus sham continuous positive airway pressure (CPAP). We discuss our results in light of previous findings and provide a comprehensive literature review. Methods: Twenty-seven treatment-naïve male patients with moderate to severe OSAS and seven healthy age- and education-matched control subjects (HC) were recruited. After a baseline fMRI scan, patients randomly received either active (therapeutic, n=14) or sham (subtherapeutic, n=13) nasal CPAP treatment for 2 months. Results: Significant negative correlations were observed between nocturnal hypoxemia duration and GMV in bilateral lateral temporal regions. No differences in GMV or WMV were found between OSAS patients and HC, and no differences between CPAP versus sham CPAP treatment effects in OSAS patients. Conclusion: It appears that considering VBM GMV changes there is little difference between OSAS patients and HC. The largest VBM study to date indicates structural changes in the lateral aspect of the temporal lobe, which also showed a significant negative correlation with nocturnal hypoxemia duration in our study. This finding suggests an association between the effect of nocturnal hypoxemia and decreased GMV in OSAS patients.